2021
DOI: 10.1098/rsbl.2021.0381
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting on time-structured acoustic stimuli in ducklings

Abstract: Filial imprinting is a dedicated learning process that lacks explicit reinforcement. The phenomenon itself is narrowly heritably canalized, but its content, the representation of the parental object, reflects the circumstances of the newborn. Imprinting has recently been shown to be even more subtle and complex than previously envisaged, since ducklings and chicks are now known to select and represent for later generalization abstract conceptual properties of the objects they perceive as neonates, including mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This use of artificial stimuli also helps to explore less intuitive properties of the content of imprinting. For instance, Monteiro et al (2021) were able to imprint domestic ducklings onto specific time-structured acoustic stimuli, while in a similar experiment, Martinho and Kacelnik (2016) showed that ducklings were able to imprint on the concept of either "same" or "different" while being exposed to various moving three-dimensional shapes. This…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This use of artificial stimuli also helps to explore less intuitive properties of the content of imprinting. For instance, Monteiro et al (2021) were able to imprint domestic ducklings onto specific time-structured acoustic stimuli, while in a similar experiment, Martinho and Kacelnik (2016) showed that ducklings were able to imprint on the concept of either "same" or "different" while being exposed to various moving three-dimensional shapes. This…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Monteiro et al. (2021) were able to imprint domestic ducklings onto specific time‐structured acoustic stimuli, while in a similar experiment, Martinho and Kacelnik (2016) showed that ducklings were able to imprint on the concept of either “same” or “different” while being exposed to various moving three‐dimensional shapes. This shows that birds can filially imprint on abstract, relational properties of their sensory input, rather than simply representing auditory or visual cues, and helps to refine the notion of what constitutes an “imprintable” target.…”
Section: Discussionmentioning
confidence: 99%
“…To track the fish centroid in real time, a colour thresholding method (Monteiro et al, 2021 ) was implemented using a custom Bonsai workflow. Video was recorded at approximately 33 fps.…”
Section: Methodsmentioning
confidence: 99%